Factors Related to Health Protocol Compliance in Banu Ayu Village During The Covid-19 Pandemic - Sherli Apriyanti; Dian Wahyuni; Eka Yulia Fitri (PENA NURSING, 2023)
Coronavirus Disease (Covid-19) is an infectious disease that spreads all over the world. One way to suppress the spread of Covid-19 is to comply with health protocols such as using masks, maintaining distance and washing hands with soap. However, some people do not comply with health protocols. The purpose of this study was determine the factors related to health protocol compliance. Quantitative research was conducted with an analytical research design and cross-sectional approach. The research samples were 200 household heads (aged 20-40 years) selected by using probability sampling method with cluster sampling technique. Data were collected by using a questionnaire. Chi Square test results showed that there was a significant relationship of knowledge (p value=0.000), attitude (p value=0.000), belief (p value=0.000) and availability of health facilities (p value=0.000) towards protocol health compliance. Improving knowledge, attitude, belief and the availability of health facilities could increase community compliance, such as by providing more attractive counseling to the community by involving public health center, village apparatus and all the people in the village.